Peter Newmark's influence on my world of languages: a personal perspective - Cambridge, Jan (The Journal of Specialised Translation, 2012)
A stalwart of the Chartered Institute of Linguists, long serving council member and Vice President, Peter was a prominent figure in the Institute for as long as I have been a member—over 20 years. Peter's character and determination have always impressed me. He was a great encourager of other people—including me. Knowing what an eminent linguist he was, I was a little wary the first time I presented my ideas about the relay of strong emotion and clients' 'ungallant' language in some PSI settings. We were at the University of Westminster during an Interpreting Division event. I was slightly surprised that he should take an interest in PSI in any case; but he sat on the front row and beamed at me like an enthusiastic small child all the way through. He was a supporter of innovation, as well as a redoubtable and tireless campaigner for the Institute and its members. Knowing how much he hated unexplained acronyms and abbreviations in text or in speech, I apologise! PSI stands for Public Service Interpreting. As a long standing contributor to The Linguist, Peter covered a wide spectrum of topics in a scholarly but very accessible manner, with wit and insight and his own firmly held opinions. Never one to shy away from starting a discussion, he once inserted his thoughts about an aspect of public service interpreting ethics and practice into his "Translation Now" pages. I wrote and explained how the matter is actually handled on the basis of our code of conduct and good practice. I remember being very touched that he not only withdrew his remarks gracefully in print but phoned me to apologise for having got it wrong. When my mobile rang, I was standing outside a bail hostel, in the rain, waiting to be let in to do an interpreting job. In those days most people who were not PSI practitioners believed that public service interpreting only took place in the courts (like the International Court of Justice at The Hague or somewhere posh like that). And here I was trying to get out of the rain so I could crouch in a cramped little room, with most of the floor space taken up by a photocopier and a coffee machine, while a legal executive took instructions from a bailed client. More recently than that, in his capacity as Chair of the Journal of Specialised Translation's Board, he was kind enough to suggest me as a guest editor for an issue of JoSTrans dedicated to Public Service Interpreting. I learned so much that year and found so many fascinating people willing to write for issue 14. I found reviewers, who were keen and interested and I had the pleasure of working with the general editorial team. I'm proud of my issue of JoSTrans and it has been beneficial to me in experience and learning. I hope Peter thought I did a decent job but I thank him anyway for the opportunity. In big ways and little ways, Peter has been a positive influence in my working life and has certainly made a long-term contribution to the Work of the Chartered Institute of Linguists.